Nature-inspired optimization algorithms - Yang, Xin-She (Elsevier insights, 2014)
Nature-Inspired Optimization Algorithms provides a systematic introduction to all major nature-inspired algorithms for optimization.The book's unified approach, balancing algorithm introduction, theoretical background and practical implementation, complements extensive literature with well-chosen case studies to illustrate how these algorithms.